2007
DOI: 10.1242/jcs.010744
|View full text |Cite
|
Sign up to set email alerts
|

Neural cell adhesion molecule regulates the cellular response to fibroblast growth factor

Abstract: Neural cell adhesion molecule (NCAM) mediates cell-cell adhesion and signaling in the nervous system, yet NCAM is also expressed in non-neural tissues, in which its function has in most parts remained elusive. We have previously reported that NCAM stimulates cell-matrix adhesion and neurite outgrowth by activating fibroblast growth factor receptor (FGFR) signaling. Here, we investigated whether the interplay between NCAM and FGFR has any impact on the response of FGFR to its classical ligands, FGFs. To this en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 44 publications
6
71
1
Order By: Relevance
“…The best characterised of these is an interaction with FGFR signalling, where, both in Drosophila and mammals, FGFR activity is required for Fas2/NCAM induced neurite outgrowth (Williams et al, 1994;Forni et al, 2004) and direct binding of NCAM activates FGFR (Kiselyov et al, 2003;Christensen et al, 2006). By contrast, and an illustration of the context dependence of such interactions, it has also recently been reported that NCAM can inhibit FGFR activation by its ligand FGF (Francavilla et al, 2007). Less well studied links between NCAM and growth factors include the observation that NCAM can act as a signalling receptor for GDNF (Paratcha et al, 2003), and that it participates in the response of oligodendrocyte precursors to PDGF (Zhang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best characterised of these is an interaction with FGFR signalling, where, both in Drosophila and mammals, FGFR activity is required for Fas2/NCAM induced neurite outgrowth (Williams et al, 1994;Forni et al, 2004) and direct binding of NCAM activates FGFR (Kiselyov et al, 2003;Christensen et al, 2006). By contrast, and an illustration of the context dependence of such interactions, it has also recently been reported that NCAM can inhibit FGFR activation by its ligand FGF (Francavilla et al, 2007). Less well studied links between NCAM and growth factors include the observation that NCAM can act as a signalling receptor for GDNF (Paratcha et al, 2003), and that it participates in the response of oligodendrocyte precursors to PDGF (Zhang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the spectrum of different types of relationships, the interaction between adhesion proteins and signalling can be cooperative or antagonistic: in some cases adhesion promotes signalling, in others it inhibits (e.g. Williams et al, 1994;Francavilla et al, 2007). Understanding the variety of relationships between signalling and adhesion is made more difficult by the fact that much of the information available has relied on cell culture and other in vitro methods.…”
Section: Introductionmentioning
confidence: 99%
“…NCAM accomplishes a similar induction of cell migration and invasion by directly binding and stimulating FGFR via its fibronectin type III domains [95]. Thereby, NCAMmediated stimulation of FGFR signaling differs substantially from FGF-induced FGFR signal transduction resulting into different cellular outcomes, such as increased cell-substrate adhesion, migration and invasion by NCAM and cell proliferation by FGF [99]. The interaction between N-cadherin and NCAM with FGFR relies on a CAM-domain proximally located to the acid box region of the FGFR, which is not required for FGF ligand binding [100].…”
Section: The Cadherin Switch and Its Consequencesmentioning
confidence: 99%
“…Peptides in either FnI or FnII are able to bind to the FGF receptor and activate ERK1/2 (Kiselyov et al, 2003;Neiiendam et al, 2004;Anderson et al, 2005;Jacobsen et al, 2008;Palser et al, 2009), whereas NCAM-Fc lacking the second Fn module fails to elicit various FGF receptor-dependent responses induced by NCAM-Fc containing the entire NCAM extracellular domain (Francavilla et al, 2007;Francavilla et al, 2009). To elucidate which of these NCAM modules are necessary for specifically stimulating focal adhesion in addition to ERK1/2, a number of different NCAM fragments were created (summarized in Fig.…”
Section: Polysia and Ncam Modulate Peripheral Focal Adhesionsmentioning
confidence: 99%